Short review and detection of Leishmania parasites in skin biopsies from patients coming from Echeandía, Bolívar Province, Ecuador - León, Renato; Erkelenz, Christina; Reck, Carlos; Terán, Rommy (ACI Avances en Ciencias e Ingenierías, 2014)
Leishmaniasis is an important neglected tropical disease and the cause of significant morbidity in endemic countries such as Ecuador. It is transmitted by the bite of infected sand flies (Diptera Psychodidae) and has been reported from at least 22/24 provinces in the country including the foothills of the Andean mountains. Herein, we report the detection of Leishmania parasites, using PCR assays, in skin biopsies taken from ulcers of leishmaniasis patients from Echeandía in the province of Bolívar, Ecuador. These results suggest that most of the patients were infected with parasites from the braziliensis complex that among other species, includes Leishmania (Viannia) panamensis which is the most common species that causes cutaneous leishmaniasis in the Pacific coast, and Leishmania (V.) braziliensis, the cause of mucocutaneous lesions and significant patient disfiguration. More studies are needed to further identify the parasite species present in this area and address aspects of the parasite’s life cycle and transmission dynamics. Our preliminary results showed that the R174 and R798 18 S ribosomal DNA primers used in this study are effective to amplify Leishmania DNA and would be a useful tool to molecularly detect New World parasites causing tegumentary leishmaniasis.
Keywords: PCR; Echeandia; leishmaniasis; skin biopsies